The ideological significance of "institutional neutrality" mandates in state-level campus speech legislation. Issue 1 (3rd July 2019) - Medeiros, Ben
ABSTRACT: This paper focuses on the "institutional neutrality" provisions commonly included in recent state-level "campus free speech" legislation. I argue that their normative promotion of "neutrality" in fact reinforces ideologies of colorblindness, neoliberal individualism, and corporate hegemony. To perform the analysis, I examine the text of the bills and the intellectual lineage from which they descend in conjunction with statements by their proponents and allies in the campus speech debates. The theoretical significance of this analysis thus lies in further interrogating how the norms of the liberal free-speech tradition are imbued with ideological meaning. Relatedly, the article shows that the logic of older critiques regarding media industry concentration and the laissez-faire "marketplace" framework can also be applied to calls for educational institutions to strive for "neutrality."